The effect of ketamine on cognition, anxiety, and social functioning in adults with psychiatric disorders: A systematic review and meta-analysis - Marchi, Mattia; Magarini, Federica Maria; Galli, Giacomo; Mordenti, Federico; Travascio, Antonio; Uberti, Daniele; De Micheli, Edoardo; Pingani, Luca; Ferrari, Silvia; Galeazzi, Gian Maria (Frontiers in Neuroscience, 2022)
Background It has been shown that ketamine can improve suicidality and depression. Evidence for other dimensions of psychopathology is lacking. We undertook a systematic review to investigate the effect of ketamine on cognition, anxiety, quality of life, and social functioning in adults with psychiatric disorders. Methods PubMed (Medline), Scopus, PsycINFO, and EMBASE were searched up to April 2022. Randomized controlled trials (RCTs) on ketamine [or its S (+) enantiomer] reporting data on cognition, anxiety, quality of life, social functioning in adults with psychiatric disorders were included. Standardized mean difference (SMD) was used for summarizing continuous outcomes. Results Twenty-two reports were included in the final selection, of which 20, corresponding to 1,298 participants, were included in the quantitative synthesis. Affective disorders were the predominant diagnostic category. Median follow-up time was 21 days. The evidence was rated moderate to very low. In most trials, ketamine was administered intravenously or as adjuvant to electro-convulsant therapy (ECT). Only 2 trials of intranasal esketamine were identified. The effect of ketamine on depression was confirmed (SMD: −0.61 [95% CI: −1.06; −0.16]). Furthermore, by pooling results of 6 RCTs, ketamine may be effective in reducing anxiety symptoms (SMD: −0.42 [95% CI: −0.84; 0.003]), particularly when administered not within ECT (5 trials; SMD: −0.58 [95% CI: −1.07; −0.09]). However, there was moderate heterogeneity of results. Patients treated with ketamine also had an improvement in social functioning (SMD: −0.31 [95% CI: −0.52; −0.10]), although the estimate was based only on 2 studies. No difference to comparators was found with respect to cognition and quality of life. Conclusion Alongside the antidepressant effect, ketamine may also improve anxiety and social functioning in adults with affective disorders.